Lactic Acid Bacteria from Mangrove Sediment Produce Bacteriocins Active Against Gram-Positive and Negative Bacteria - Kusharyati, Dyah Fitri; Ariaputri, Fira Julian; Pramono, Hendro; Rovik, Anwar (UIN Sunan Gunung Djati Bandung, 2023)
Mangrove is a unique ecosystem. Only a few studies have explored the presence of lactic acid bacteria and their roles in mangrove ecosystems. From mangrove sediments at Logending Beach in Jawa Tengah (Indonesia), the Lactic Acid Bacteria (LAB) isolates LG-50, LG-107, and LG-114 were discovered. They produce bacteriocins. This study aimed to determine the characteristics of LAB isolates, antimicrobial activity, and physicochemical properties of bacteriocins. LAB isolates were characterized by morphology, physiology, and biochemistry. The production of bacteriocin was performed by salting-out method, followed by testing its antimicrobial activity against pathogenic bacteria. Isolates LG-50, LG-107, and LG-114 are thought to be in the Lactobacillus group. The crude bacteriocin can inhibit the growth of Gram-positive and negative bacteria. The average inhibition zones against Escherichia coli and Staphylococcus aureus were 16.67 mm and 22.17 mm, respectively. The crude bacteriocin tested positive for ninhydrin. It confirmed the crude bacteriocin was a protein and sensitive to the proteolytic enzyme. SDS-PAGE analysis presented the molecular weight of crude bacteriocin was 38 kDa. This present study supports the potential use of bacteriocin in the pharmaceutical and food industries.